Social awareness and relational skills of students as implications of social emotional learning based on tri hita karana - Kristiani, Putu Ery; Astawa, Ida Bagus Made; Mudana, I Wayan (Jurnal Penelitian Ilmu Pendidikan, 2025)
Character education is a key pillar of global education reform, encompassing moral, spiritual, and social values. This study investigates the effectiveness of Social Emotional Learning (SEL) based on Tri Hita Karana (THK) values in improving students’ social awareness and relational skills. A quasi-experimental design was used with eighth-grade students and social studies teachers as subjects, and data were collected through observations, surveys, and document analysis. Descriptive and inferential analyses (including t-tests and MANOVA) were conducted. The outcomes show that incorporating THK values into SEL resulted in high levels of social awareness among students as well as significant improvements in their relational skills. Statistical tests confirmed that students in the SEL-THK (SEL based on Tri Hita Karana) group had significantly higher social awareness and relational skill outcomes than those in conventional learning. Moreover, the implementation of SEL based on THK values had a significant simultaneous positive effect on both social awareness and relational skills. These findings suggest that a THK-based SEL approach can holistically enhance key social-emotional competencies in students.